The arteriolar injury in hypertension. (February 2018) - Gu, Qian Ru; Li, Yang Yang; Chen, Guo Rong; Quinn, M.J.
Abstract: In 1937, Drs. Moritz and Oldt described arteriolar injuries in the kidneys (and other viscera) in hypertension, across the age range, in both sexes, and, in different races. This hypothesis proposes that injuries to vasomotor nerves cause the arteriolar injury in the kidney in hypertension, (as well as that in the uterus in preeclampsia). Different patterns of perivascular hyalinisation in different viscera are clues to the varying causes and consequences of arteriolar injury. In the uterus there is a symmetrical, perivascular "halo of hyalinisation" that marks the lines of extension of regenerating, injured nerves to the placental bed, whereas in the kidney there is a disordered and asymmetrical "halo of hyalinisation" where persistent, and recurrent, increases in intravascular pressures interrupt development of regenerating nerves. Consequences of injuries to vasomotor nerves include releasing a "soup" of cytokines that cause regeneration of "new" nerves expressing primitive, pain and stretch receptors including TRPV-1 and P2X3 purinergic "stretch" receptors that may be significant in the afferent mechanism in preeclampsia. There is also concurrent, "background" hyperplasia of denervated tunica media and intima leading to narrowing of the arterioles and a further drive to hypertension through renal ischaemia (Goldblatt, 1942). These observations require support from animal studies and other investigations to establish causation. This hypothesis may provide a number of potential mechanisms that reinforce, or accelerate, the physiological processes that contribute to hypertension.